Suitability For Self-Studies Of The Newly Introduced Grade 7 Mathematics Textbook In Sri Lanka - Hendadura Chandima Kumari De Zoysa (International Journal on Emerging Mathematics Education, 2022)
Textbooks play a prominent role in the teaching and learning process in developing countries like Sri Lanka. Mathematics textbooks could be the most important tool in a classroom environment of teaching and learning Mathematics. Several challenges of teaching and learning Mathematics have been identified in the Sri Lankan education system such as existence of teachers without adequate teacher training in Mathematics, teacher deployment issues, and severe shortage of competent Mathematics teachers in many schools. Therefore, it was observed that the Mathematics textbook is using as a hand book in Sri Lankan schools.Â  Consequently, there is a huge need for providing highly effective textbooks to aid student learning. Further, it was decided to evaluate and to determine strengths and weaknesses of the Mathematics text books starting from Grade 7 for the first time in 2016. Therefore, it is essential to evaluate the features of the newly introduced Grade 7 Mathematics textbook, in 2016 for the local syllabus. For this purpose, 550 students from three different zonal education offices in Galle district took part in this study. Data collection was carried out through an assessment. The data was analyzed through descriptive statistics. Further, it was tested for the significance using the one sample T-test. According to the results, it suggests that the newly introduced Grade 7 Mathematics textbook in Sri Lanka helps to studentsâ€™ self-studies than the old one.